Sentidos da educação musical na formação acadêmico-profissional do pedagogo - Dallabrida, Iara Cadore (2015)
This research is part of the research line Education and Arts of Postgraduate Program in Education of Federal University of Santa Maria and was developed along with FAPEM Formação, Ação e Pesquisa em Educação Musical research group. The research aimed, as main objective, to comprehend the meanings (VYGOTSKY, 2009) attributed by undergraduates in the Pedagogy Major at UFSM to the music education in their professional-academic formation. The investigation followed methodological paths of qualitative approach, consisting of a case study (YIN, 2010) which had as instrument of data production five direct participant observations in Early Child Music Education classrooms, in the referred major, as well as the realization of individual interviews with six undergraduates in this discipline, during the development of this research. The observations were written in a Field Diary (TRIVIÑOS, 1987; LIMA; MIOTO, DAL PRÁ, 2007). The study was analyzed in meaning nuclei (AGUIAR; OZELLA, 2006; 2013), aiming at apprehending the meanings produced by the subjects. The resulting analytical categories refer to some of the contexts lived by the undergraduates, which constitute needs, motifs (REY, 2003; RODRIGUES; LUSTOSA, 2010) and meanings about music education in its professional-academic formation: Higher Education and labor market; Pedagogy Major relation between theory and practice; Musical Education in the Pedagogy Major; and Music in the undergraduates‟ personal and professional life. The theoretical framework that founded this research was anchored in five themes: (1) Meanings, according to Vygotsky (2009) and authors who have studied him (COSTAS; FERREIRA, 2011; ZUIN, 2011; AGUIAR; OZELLA, 2013); (2) Higher Education and its relation to the labor market (NOGUEIRA, 2012; FÁVERO; SGUISSARDI, 2012) and adult formation (ZABALZA, 2004); (3) the Pedagogy Major as locus of professional-academic formation of Child and Early Child Basic Education teachers (BRASIL, 2006); (4) Music Education in Pedagogy Major in Brazil (FIGUEIREDO, 2001; 2003; 2004; FURQUIM, 2008; CISZEVSKI, 2010) specifically in the Pedagogy Major at UFSM (BELLOCHIO, 2000; SPANAVELLO, 2005; CORREA, 2008; WERLE, 2010, OESTERREICH, 2010; DALLABRIDA, 2013); and (5) Music social meanings (SOUZA, 2002; LOUREIRO, 2003; HUMMES, 2004; HENTSCHKE et al, 2009; FREIRE, 2011; AMATO, 2012). We have concluded that the meanings attributed to music education in the Pedagogy Major at UFSM are related to meanings of Music associated to affectivity: to entertainment, to the construction of interpersonal relations and identities, to the expression of thoughts, emotions and feelings. Collaborative work developed in the disciplines of Music and Drama has enriched the meanings of Early Child Music Education discipline, in the Pedagogy major, constituting meanings about music education in this formative moment, according to the undergraduates.